Mapping the corticoreticular pathway from cortex‐wide anterograde axonal tracing in the mouse. Issue 12 (22nd October 2021) - Boyne, Pierce; Awosika, Oluwole O.; Luo, Yu
Abstract: The corticoreticular pathway (CRP) has been implicated as an important mediator of motor recovery and rehabilitation after central nervous system damage. However, its origins, trajectory and laterality are not well understood. This study mapped the mouse CRP in comparison with the corticospinal tract (CST). We systematically searched the Allen Mouse Brain Connectivity Atlas (© 2011 Allen Institute for Brain Science) for experiments that used anterograde tracer injections into the right isocortex in mice. For each eligible experiment ( N  = 607), CRP and CST projection strength were quantified by the tracer volume reaching the reticular formation motor nuclei (RFmotor ) and pyramids, respectively. Tracer density in each brain voxel was also correlated with RFmotor versus pyramids projection strength to explore the relative trajectories of the CRP and CST. We found significant CRP projections originating from the primary and secondary motor cortices, anterior cingulate, primary somatosensory cortex, and medial prefrontal cortex. Compared with the CST, the CRP had stronger projections from each region except the primary somatosensory cortex. Ipsilateral projections were stronger than contralateral for both tracts (above the pyramidal decussation), but the CRP projected more bilaterally than the CST. The estimated CRP trajectory was anteromedial to the CST in the internal capsule and dorsal to the CST in the brainstem. Our findings reveal a widespread distribution of CRP origins and confirm strong bilateral CRP projections, theoretically increasing the potential for partial sparing after brain lesions and contralesional compensation after unilateral injury. Abstract : The mouse corticoreticular pathway (CRP) originates from widespread parts of the cortex, including the primary motor (M1), secondary motor (M2), anterior cingulate, medial prefrontal, and primary somatosensory (S1) areas. Compared with the corticospinal tract, the CRP is more distributed and bilaterally projecting, suggesting greater resilience to complete disruption.